SPEECH ACTIONS OF JAPANESE COMMANDS IN ANIME ASSASSINATION CLASSROOM - Sisin Liswinda; Syahrial; Diana Kartika; Irma (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2023)
The Japanese language cannot be separated from acting speech in communicating with people around it. Directive speech acts have various types, one of which is commands. The speech act of the command directive expresses the attitude of the speaker towards the actions that the speech opponent must take in order to perform the speaker's wishes. This study aims to describe the form and function of command directive speech acts contained in the assassination classroom anime film. The source of data in this study is the anime film Assassination Classroom. This type of research is qualitative research. The data collection methods and techniques in this study are listening methods and recording techniques and then analyzed using the agih method and the Direct Element Sharing (BUL) technique. The results of the study found that there were as many as 23 data as follows: the form te kudasai as many as 10 data with the function of commanding and shirking, the form of mashou as many as 5 data with the function of commanding, the form of youni as many as 3 data with the function of commanding.